2022
DOI: 10.1371/journal.pone.0264560
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal target size perturbations during grasping movements are described by subsequent size perception and saccade amplitude

Abstract: Perception and action are essential in our day-to-day interactions with the environment. Despite the dual-stream theory of action and perception, it is now accepted that action and perception processes interact with each other. However, little is known about the impact of unpredicted changes of target size during grasping actions on perception. We assessed whether size perception and saccade amplitude were affected before and after grasping a target that changed its horizontal size during the action execution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Custom MATLAB algorithms (The MathWorks, Massachusetts, United States) were created to compute three-dimensional marker velocities and subsequently calculate the distance between index and thumb markers (known as manual estimate aperture, see Figure 1C ). As in our previous work ( Sanz Diez et al, 2022 ), to estimate participants’ horizontal size perception, manual estimate aperture values were solely considered in those time periods where index and thumb marker velocities were below 5 mm/s. Within those intervals, the manual estimate aperture was identified as the maximum index-thumb distance.…”
Section: Methodsmentioning
confidence: 99%
“…Custom MATLAB algorithms (The MathWorks, Massachusetts, United States) were created to compute three-dimensional marker velocities and subsequently calculate the distance between index and thumb markers (known as manual estimate aperture, see Figure 1C ). As in our previous work ( Sanz Diez et al, 2022 ), to estimate participants’ horizontal size perception, manual estimate aperture values were solely considered in those time periods where index and thumb marker velocities were below 5 mm/s. Within those intervals, the manual estimate aperture was identified as the maximum index-thumb distance.…”
Section: Methodsmentioning
confidence: 99%
“…Although the perceptual phase before and after grasping execution applied to the same target that, in these two moments of the task, was identical in size, they found that, after the grasping action, reports regarding perceptual size showed significant differences that depended on the type of size change that occurred during movement execution. In fact, as shown in Figure 7 , observers reported a smaller size perception when the visual target was lengthened during the grasping execution and no perception modification when the visual target was shortened during the grasping execution (Sanz Diez et al, 2022 ). In both of the studies described above, the perceptual modification occurred according to the type of movement (i.e., reaching or grasping) and to the unpredictable changes of target size during the movement itself, suggesting that this modification can be considered to be a descriptive parameter of the previous motor action (Bosco et al, 2017 ; Sanz Diez et al, 2022 ).…”
Section: The Effect Of Action Execution On Perceptionmentioning
confidence: 99%
“…In fact, as shown in Figure 7 , observers reported a smaller size perception when the visual target was lengthened during the grasping execution and no perception modification when the visual target was shortened during the grasping execution (Sanz Diez et al, 2022 ). In both of the studies described above, the perceptual modification occurred according to the type of movement (i.e., reaching or grasping) and to the unpredictable changes of target size during the movement itself, suggesting that this modification can be considered to be a descriptive parameter of the previous motor action (Bosco et al, 2017 ; Sanz Diez et al, 2022 ).…”
Section: The Effect Of Action Execution On Perceptionmentioning
confidence: 99%
See 2 more Smart Citations